2021
DOI: 10.3390/nu13062070
|View full text |Cite
|
Sign up to set email alerts
|

Association of Heavy Metals with Overall Mortality in a Taiwanese Population

Abstract: Previous studies have shown links between heavy metals and many health issues. However, data on the association between heavy metals and mortality in the general population are still limited. Therefore, the aim of this study was to investigate the relationship between heavy metals and overall mortality in the general population. We enrolled 2497 participants (1001 males and 1496 females) living in southern Taiwan, and measured levels of seven heavy metals: lead (Pb) in blood and cadmium (Cd), nickel (Ni), copp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 37 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…The total of 1,801 subjects in 2016 (Wave-1) and 1,927 subjects in 2018 (Wave-2) had the data of urinary TAs, analyzed by one central laboratory (the Union Clinical Laboratory (UCL)) in Taipei, Taiwan officially accredited by Taiwan Accreditation Foundation, with its certification effective between 16 March 2015and 15 March 2018. The detailed study design of the Wave-1 and Wave-2 has been published previously (Tsai H. et al, 2021;Liu et al, 2021). Because the majority of voluntary subjects in the three-wave surveys were adults, only subjects whose ages ≥18 years (n = 1,801 for Wave-1; n = 1,695 for Wave-2; n = 116 for Wave-3) were included in this study.…”
Section: Three-wave Health Check-up In Six Villages Close To Lin-hai ...mentioning
confidence: 99%
“…The total of 1,801 subjects in 2016 (Wave-1) and 1,927 subjects in 2018 (Wave-2) had the data of urinary TAs, analyzed by one central laboratory (the Union Clinical Laboratory (UCL)) in Taipei, Taiwan officially accredited by Taiwan Accreditation Foundation, with its certification effective between 16 March 2015and 15 March 2018. The detailed study design of the Wave-1 and Wave-2 has been published previously (Tsai H. et al, 2021;Liu et al, 2021). Because the majority of voluntary subjects in the three-wave surveys were adults, only subjects whose ages ≥18 years (n = 1,801 for Wave-1; n = 1,695 for Wave-2; n = 116 for Wave-3) were included in this study.…”
Section: Three-wave Health Check-up In Six Villages Close To Lin-hai ...mentioning
confidence: 99%
“…Some metals, such as iron, zinc, copper, cobalt and manganese, are required for various physiological functions in humans at low concentrations, but they become toxic at higher concentrations. Other HMs, such as cadmium and lead, are not known to have any beneficial effects on human health and their accumulation in the human body is deleterious to health [ 29 ]. It is well known that exposure to HMs can cause hemopoietic, cardiovascular, gastrointestinal, respiratory, reproductive, renal and neurological disorders [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that Ni can cause oxidative stress, inflammatory responses, and apoptosis in vivo and in vitro. [6][7][8][9][10] In vivo studies, report that NiCl 2 causes oxidative stress and induces hepatotoxicity in broiler chickens by activating mitochondria-mediated apoptotic pathways. 11 The in vitro study conducted by Wang et al concluded that Ni induces cytotoxicity and apoptosis via a reactive oxygen species-(ROS-) and mitochondriadependent pathway in human proximal tubule cells.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to examine the toxic effects of these compounds and identify the underlying mechanisms. Numerous studies have shown that Ni can cause oxidative stress, inflammatory responses, and apoptosis in vivo and in vitro 6–10 . In vivo studies, report that NiCl 2 causes oxidative stress and induces hepatotoxicity in broiler chickens by activating mitochondria‐mediated apoptotic pathways 11 .…”
Section: Introductionmentioning
confidence: 99%